Healthcare built environment and behavioural and physiological indicators of stress responses in autism spectrum disorder: Protocol for a mixed-methods systematic review - Billie Weaver; Evangelia Chrysikou; Mar García-Rodríguez; Daryia Palityka; Eva Hernandez-Garcia (PLoS ONE, 2026)
Introduction Autistic populations are more likely to need healthcare (HC) services due to co-occurring mental health issues, including anxiety and attention-deficit hyperactivity disorders. One of the most significant barriers to delivering optimal medical procedures in autism spectrum disorder (ASD) is the sensory overload in HC settings. Divergent sensory processing, along with unpredictable built environments (BEs), can exacerbate stress-induced anxiety and avoidant behaviour. A growing body of systematic studies links autism-friendly BEs with positive care experiences, yet substantial gaps remain in understanding the effects on behavioural and physiological aspects of emotional responses. This systematic review aims to comprehensively evaluate the HC-BE features that impact on behavioural indicators and non-invasive biomarkers of stress, anxiety and sensory processing in patients with ASD, to establish best practices. Methods and analyses The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines will be followed. Peer-reviewed articles in PubMed, Embase, Web of Science, Scopus, and PsycINFO databases and Google Scholar will be searched. Studies will be selected if they apply qualitative, quantitative, or mixed-methods designs. Two independent reviewers will select studies at the title and abstract, and full-text screening stages. Data will be extracted by one reviewer and verified by review members using a crowdsourcing approach for quality assurance. Risk of bias will be assessed by one reviewer using the Cochrane Risk of Bias Tools, The Critical Appraisal Skills Programme, and The Mixed Methods Appraisal Tool, and checked by the reviewer with methodological expertise. A results-based convergent synthesis design is planned for data synthesis. Discussion This review, which converges indicators and patient experiences, will provide a complete overarching picture of the inherent complexities associated with HC-BE and autistic individuals. The findings can inform decisions and recommendations for research and practice. Trial registration PROSPERO CRD42024562288